Opportunities and Challenges in Developing Livestock Waste as Transportation Fuel - Mustovia Azahro; Dayu Lingga Lana; Ridho Adi Negoro; Ira Amanda Hirbasari (Institut Pertanian Bogor, 2025)
In 2023, Indonesia became a top 10 carbon emitter, which is contradictory to its net zero emissions agenda. One of the causes is the use of fossil energy, and it is necessary to transition energy sustainably, especially for the transportation sector, which is the largest contributor to emissions. New renewable energy sources from livestock manure waste can be used as fuels in the transportation sector. Many livestock produce waste that needs to be utilized. Livestock manure waste is widely used as biogas for household-scale applications but is rarely utilized as a biofuel in the transportation sector. This study aimed to analyze the potential and challenges of developing biofuels from livestock waste in Brebes Regency (Indonesia). Biofuel development must be conducted at the regional level to support the acceleration of greenhouse gas emission reduction targets. This research uses data sources in the form of literature studies and interviews, the Analytical Hierarchy Process was used to formulate sustainable energy transition policies. The results of this study describe the opportunities and challenges of developing livestock manure waste as transportation fuel. The Brebes Regency Government can encourage this through policies to accelerate the energy transition. Keywords: biogas, energy transition, livestock waste, transportation fuel